Predictors of failure of high flow nasal cannula failure in acute hypoxemic respiratory failure due to COVID-19. (August 2021) - Garner, Orlando; Dongarwar, Deepa; Salihu, Hamisu M.; Barrantes Perez, Jairo H.; Abraham, Jocelyn; McBride, Cameron; Mathew, Sindhu; Antony, Preethi; Collins, Keegan; Richards, Katherine L.; Howard, Christopher M.
Abstract: Hypoxemic respiratory failure is a common manifestation of COVID-19 pneumonia. Early in the COVID-19 pandemic, patients with hypoxemic respiratory failure were, at times, being intubated earlier than normal; in part because the options of heated humidified high flow nasal cannula (HFNC) and non-invasive ventilation (NIV) were considered potentially inadequate and to increase risk of virus aerosolization. To understand the benefits and factors that predict success and failure of HFNC in this population, we evaluated data from the first 30 sequential patients admitted with COVID-19 pneumonia to our center who were managed with HFNC. We conducted Cox Proportional Hazards regression models to evaluate the factors associated with high flow nasal cannula failure (outcome variable), using time to intubation (censoring variable), while adjusting for comorbidities and immunosuppression. In the majority of our patients (76.7%), the use of HFNC failed and the patients were ultimately placed on mechanical ventilation. Those at increased risk of failure had a higher sequential organ failure assessment score, and at least one comorbidity or history of immunosuppression. Our data suggest that high flow nasal cannula may have a role in some patients with COVID-19 presenting with hypoxemic respiratory failure, but careful patient selection is the likely key to its success.